Prevalence of MRSA nasal carriage among pregnant women in Copenhagen. - Mona Katrine Alberthe Holm; Thilde Nordmann Winther; Sisse Kammann; Marianne Skovby Rasmusson; Lis Brooks; Henrik Westh; Mette Damkjær Bartels (PLoS ONE)
Background Methicillin resistant Staphylococcus aureus (MRSA) frequently causes outbreaks in neonatal intensive care units (NICUs). It is believed that MRSA predominantly enters the NICU with MRSA colonized parents. In Denmark, 27 MRSA NICU outbreaks have been registered between 2008 and 2019. Aim The aim of this study was to determine the prevalence of MRSA nasal carriage in pregnant women in Copenhagen and to clarify if MRSA screening during pregnancy could add to the prevention of NICU outbreaks. Methods All pregnant women 18 years or older were offered MRSA nasal screening at their first midwife visit between 13 and 20 weeks of gestation. Results 1778 pregnant women were included, two (0.11%) carried MRSA in the nose. Conclusion Infants of the two MRSA positive women were not admitted to a NICU and therefore the screening had no impact on NICU outbreaks. The low prevalence of MRSA found in this study does not justify MRSA screening of all pregnant women in Denmark.